Wage gaps large and small - Barry T. Hirsch (Institute for the Study of Labor (IZA), 2008)
The law of one wage does not strictly hold, nor should it be expected to hold, in contemporary labor markets. The law of one wage, however, provides a surprisingly good first approximation of the structure of U.S. wages. This generalization is drawn from research on a diverse set of topics: the Mincerian wage equation and earnings imputation, union wage differentials, product market regulation and the labor market, wages in male and female jobs, the wage effects of military service, and interarea wages and cost-of-living.
Keywords: J01; 330; Wage differentials; imputation; unions; cost-of-living; regulation; wages; Lohnstruktur; Lohnbildung; Lohndrift; Lohndifferenzierung; USA